MAKNA SIMBOL BUSANA TARI PENYAMBUTAN PENGANTIN DAYAK TAMAN DI KABUPATEN KAPUAS HULU KALIMANTAN BARAT - Gabriella Rami; Imma Fretisari; Asfar Muniir (Universitas Tanjungpura, 2020)
AbstractThis research aims to describe the meaning symbols of Penyambutan Pengantin dayak Taman dance costume in Kapuas Hulu. The research focused issues related to meaning symbols about color, motifs, and forms in the dance costume of Penyambutan Pengantin Dayak Taman Kabupaten Kapuas Hulu.Method used was a description with a qualitative form, the approach used is semiotics. The sources data in this research were the results of interview, firld notes and documentation with the speakers, namely Eugene Yohanes, Yuliana Langki, and Yakoba. Validity data testing technique used was source triangulation. The data analysis techniques used in this research are the sistematic compiling and analyzing. The results from this research was a Batang lalo that has the meaning symbols of gathering of men and women in a marriage that is a complete and unbroken and also as a symbol of fertility and a prayer for the bride and groom’s new life. Motif kaki burung that have the significance of the symbol as a foothold or power to build a home that will have many obstacles in the future that a family must face. The meaning symbol of the colored in dance costume was a cycle of human life. Keywords: The Meaning of The Symbol, Penyambutan Pengantin Dayak Taman Dance Costume